IMPLEMENTASI PROGRAM ENGLISH DAY TERHADAP KEMAMPUAN BERBAHASA ASING DAN DAYA INGAT SISWA SEKOLAH DASAR - ridha addiina soraya; Ahmad Suriansyah; Arta Mulya Budi Harsono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English is an international language that plays an important role in the current era of globalization.Therefore, English should be introduced and taught from an early age. This study aims to explore the implementation of the English Day program at SDN Kebun Bunga 5 and its impact on students’ foreign language skills and memory. The research employed a qualitative approach with a case study design.The primary data were collected through interviews with the principal and English teacher, as well as through field observations involving all students who participated indirectly in the data collection process. The results of the study show that the implementation of the English Day program has a positive impact on students’ English language skills and memory at SDN Kebun Bunga 5.